Decontaminating Planar Regions with Finite Automaton Robots and Tiles - N., N.

Load-Balanced Routing in Hybriden Kommunikationsnetzwerken - Wulfes, Robin

Monotone Suchbarkeit bei den selbststabilisierenden Protokollen Build-List und Build-Multilist mit systemverlassenden Knoten - Jochmaring, Moritz

Untersuchungen zum Cone-Hashing - Burkhardt, Michél

An Asynchronous Adaption of a Churn-resistant Overlay Network - Banh, Ngoc Chi

Monotone Suchbarkeit in mehrdimensionalen verteilten Datenstrukturen - Schenk, Andreas

Visualisierung zu Algorithmen verteilter Netzwerksysteme - Beckendorf, Björn

MultiSkipList: A Self-stabilizing Overlay Network with Monotonic Searchability maintained - Luo, Linghui

Self-* Algorithms for Distributed Systems - Strothmann, Thim Frederik

Routing in Hybrid Communication Networks with Holes - Considering Bounding Boxes as Hole Abstractions - Sundermeier, Jannik

A Self-Stabilizing Protocol for Graphs of Diameter Two - Knollmann, Till

Self-Stabilizing Spanners for Tree Metrics - Götte, Thorsten

Nibbler: Implementing a Turing machine to simulate the Busy Beaver problem - Heuchler, Sebastian

Aggregation in Overlay Networks - Hinnenthal, Kristian
We consider the problem of aggregation in overlay networks. We use a synchronous time model in which each node has polylogarithmic memory and can send at most a polylogarithmic number of messages per round. We investigate how to quickly compute the result of an aggregate functionf over elements that are distributed among the nodes of the network such that the result is eventually known by a selected root node. We show how to compute distributive aggregate functions such as SUM, MAX, and OR in time $O(\log n / \log\log n)$ using a tree that is created in a pre-processing phase. If only a polylogarithmic number of data items need to be aggregated, we show how to compute the result in time $O(\sqrt{\log n / \log\log n})$. Furthermore, we show how to compute holistic aggregate functions such as DISTINCT, SMALLEST(k) and MODE(k) in time $O(\log n / \log\log n)$. Finally, we show a lower bound of $Ω(\sqrt{\log n / \log\log n})$ for deterministic algorithms that compute any of the aggregate functions in the scope of the thesis.

Insider-resistent Distributed Storage Systems - Eikel, Martina

Dynamics and Efficiency in Topological Self-Stabilization - Koutsopoulos, Andreas

Distributed Data Structures and the Power of topological Self-Stabilization - Kniesburges, Sebastian

Monotonic Searchability for distributed sorted Lists and De Bruijn Graphs - Feldmann, Michael

Covering and Bridging im selbstorganisierenden Partikelsystem Amoebabot - Götte, Thorsten

3D-Nesting in der SLM-Technologie - Isenberg, Daniel